Interannual variability of the atmospheric circulation and temperature anomalies in the Eastern Europe in winter - Polonsky, A.B.; Kibalchich, I.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
Using NCEP re-analysis and routine meteorological observations for 1950–2012, it is shown that the maximum impact on the winter monthly air temperature anomalies in the North-western part of the Eastern Europe is due to the North Atlantic Oscillation (NAO), while in the Eastern part to the Scandinavian pattern (SP). Typical monthly air temperature anomalies due to these modes reach 4–5 ºC. In the Black Sea region, the influence of Eastern Atlantic (EAO) and Eastern-Atlantic/Western-Russian (EAWR) oscillations dominates. Associated monthly anomalies of the regional air temperature reach 2–2.5 ºC. Positive phase of NAO and EAO is accompanied by positive temperature anomalies over the major proportion of the Eastern Europe, while the same phase of SP and EAWR oscillations – by negative ones. Negative temperature extremes in January-February are mostly observed, when EAO- and SP+ phases coincide, while positive extremes occur when EAO+ and SP- phases are observed simultaneously.